SEMIOTIC ANALYSIS OF LOGO USE ON THE ONLINE TRANSPORTATION APPLICATION - Lilik Damayanti; Abdul Gafur (Universitas Widyatama, 2022)
With the number of online transportation companies, there will be competition to attract consumer interest. Each company has its own way of introducing the products or services that they offer, from designing a logo that is used as a brand for the company until the features that can attract consumer interest. The use of Logo as a brand of the company is a point of identification; and symbols that customers use to identify their brand. Ideally, each company creates the logo so that it can directly connect consumers with the company. The purpose of this research is to dig out what is the meaning of logo or symbol of online transportation providers as the company's identity based on the colors and fonts used. Through a qualitative approach, data is obtained from a sample of logos issued officially from the largest online transportation service company in Indonesia, there are Gojek, Uber, Grab, and Maxim. The findings of this research is the Logo’s meaning of each online transportation providers represent their character based on font and color use. Most of them used wordmarks as the character and identity to be easily recognized by the public, and to convey brand attributes and brand positioning. The color that mostly used by the online transportation company is green and black as the dominant color as a symbol of their existence for tired people, means that they can be the solution for their movement, and also immovable, means that they are strong and undefeated. While font use by those company are sans serif and Egyptian, if we compare between the use of color and font, they have same purposes which shown as a symbol of strong and efficient.